IDENTIFIKASI GEN TEM ISOLAT KLINIK Escherichia coli PENGHASIL ESBLs DI RSUD Dr. SOETOMO SURABAYA - Yulianto Ade Prasetya (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2017)
Escherichia coli producing Extended Spectrum Beta Lactamases (ESBLs) can turn off the cephalosporin third and fourth generation and monobactam (aztreonam). E.coli producers ESBLs who encoded by TEM genes can hydrolyzed ampicillin, cephalontin, and cephazolin. The purpose of this research is to identify the existence of TEM genes from some space at RSUD Dr. Sooetomo Surabaya which has never been previously reported. The kind of research that used is observational descriptive with the approach genetic molecule. About thirty isolate clinical E.coli ESBLs producers of urine patients in January and February 2014 done with amplification of PCR, electrophoresis, and the result visualized on agarose gel 1.5%. The result was ten isolates (30%) positively containing TEM genes and most common to find in the Interna Department.Keywords: ESBLs, Escherichia coli, RSUD Dr. Soetomo Surabaya, TEM